2020
DOI: 10.1002/jmrs.423
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 Pandemic – considerations and challenges for the management of medical imaging departments in Queensland

Abstract: The purpose of this commentary was to outline several key considerations and challenges for medical imaging departments during a global pandemic. Five public hospital medical imaging departments were identified in South‐East Queensland, Australia, to provide insight into their response to the COVID‐19 pandemic. Common themes were identified, with the four considered most pertinent documented in this commentary. Similar operational considerations and challenges were identified amongst all sites. This commentary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 11 publications
3
45
1
Order By: Relevance
“…This posed a challenge to even a large hospital — where Singapore’s largest acute tertiary referral medical centre had to acquire additional mobile units to meet the increasing clinical demands[ 55 ]. A similar challenge was also noted in South-East Queensland, Australia where purchase, rapid acquisition and deployment of additional mobile units were initiated[ 65 ].…”
Section: Challenges In the Provision Of Medical Imaging Service During Covid-19mentioning
confidence: 79%
“…This posed a challenge to even a large hospital — where Singapore’s largest acute tertiary referral medical centre had to acquire additional mobile units to meet the increasing clinical demands[ 55 ]. A similar challenge was also noted in South-East Queensland, Australia where purchase, rapid acquisition and deployment of additional mobile units were initiated[ 65 ].…”
Section: Challenges In the Provision Of Medical Imaging Service During Covid-19mentioning
confidence: 79%
“…23 Workplaces in Australia have adopted a range of strategies to support the well-being of radiographers and radiation therapists. These included prioritising safety of vulnerable staff by encouraging working from home, 30 redeployment to a lower risk work area or taking leave, 27 daily communication with all staff, 27 regular check-in with staff working from home, 30 CARE Champions, 30 and virtual morning teas and after work drinks. 30 Approximately half (54.3%) of respondents in this study strongly agree or agree that there are adequate psychosocial support structures at work.…”
Section: E D I C a L R A D I A T I O N P R A C T I T I O N E R S A R E A P A R T O F T H E M A J O R F R O N T L I N E H E A L T H C A R mentioning
confidence: 99%
“…Besides, the genome sequencing brie ng con rmed that many cases in northern Melbourne were related to con rmed cases in quarantine hotels (17,18). The resulting outbreak, which was responsible for 768 deaths and 18,418 cases (19), re ecting inadequate contact tracing of 3763 cases of local transmission (14). A parliamentary investigation found that the Victorian government was stubbornly reluctant to accept the new digital contact tracing system with a manual data entry process at the beginning, which is unsuitable for tracking contacts.…”
Section: Public Health Responsementioning
confidence: 99%